Funding rebellion: The Rebel Contraband Dataset. (September 2018) - Walsh, James Igoe; Conrad, Justin M; Whitaker, Beth Elise; Hudak, Katelin M
We introduce a new dataset measuring if and how rebel groups earn income from the exploitation of natural resources or criminal activities. The Rebel Contraband Dataset makes three contributions to data in this area. First, it covers a wide range of natural resources and types of crime. Second, it measures rebel engagement in these activities over time. Third, it distinguishes among different strategies that rebel groups employ, such as extortion and smuggling. Theory suggests that reliance on natural resource wealth should lead rebels to mistreat civilians, but cross-group research using existing data does not find support for this relationship. We replicate an earlier study using data from the Rebel Contraband Dataset and conclude that there is a consistent relationship between natural resource exploitation and civilian victimization. Future research can use the dataset to explore questions about the onset, location, severity, and outcomes of civil conflicts.